Does Domestic Violence Jeopardize the Learning Environment of Peers within the School? Peer Effects of Exposure to Domestic Violence in Urban Peru - Italo A. Gutierrez; Oswaldo Molina (Institute of Labor Economics (IZA), 2020)
This study builds on the findings of Carrell and Hoekstra (2010, 2018) by exploring the peer effects of domestic violence exposure over the academic attainment of secondary school students in Peru. However, we also study these peer effects over a novel set of outcomes: internalizing behaviors and forms of violence at school. Our results show that being in a classroom with peers exposed to domestic violence leads to increased dropout and school mobility rates; increased levels of depression, isolation, victimization from bullying and attitudes towards violence at school; and lower verbal and math test scores. We also find no evidence that internalizing behaviors and forms of violence at school constitute mediators through which peer exposure to domestic violence affects test scores.
Keywords: D62; I21; J12; J13; 330; domestic violence; peer effects; bullying; education; internalizing behaviors